Rain reign - Martin, Ann M., 1955- (2014)
Rose Howard is obsessed with homonyms. She's thrilled that her own name is a homonym, and she purposely gave her dog Rain a name with two homonyms (Reign, Rein) which, according to Rose's rules of homonyms, is very special. Struggling with Asperger's, Rose shares a bond with her beloved dog, but when the dog goes missing during a storm, Rose is forced to confront the limits of her comfort levels, even if it means leaving her routines in order to search for her pet.
Who I am - a girl named Rose (Rows) -- My dog, Rain (Reign, Rein) -- The rules of homonyms -- Some things about my father, whose name, Wesley Howard, does not have a homonym -- When we got rain -- Who I wait for -- Why I don't ride the bus -- In my classroom -- Mrs. Leibler, who sits next to me -- Anders isn't following the rules -- When Rain went to school -- Some more about homonyms -- At the end of the day -- The storm on the weather channel -- Where we live -- How to get ready for a hurricane -- Waiting -- Storm sounds -- Rain doesn't come when I call -- Why I get mad at my father -- Rain's nose -- What must have happened -- Why my father gets mad at me -- I telephone Uncle Weldon -- How to look for a lost dog -- Someone calls me ma'am -- My story is such a sad one -- Riding with Uncle Weldon -- What to do when you think of a new homonym -- Empty space -- The good phone call -- The Happy Tail Animal Shelter in Elmara, New York -- What a microchip is -- What Mrs. Caporale says -- The thing I have to do -- Mrs. Kushel's helpful suggestions -- Where Rain used to live -- The general store in Gloverstown -- Found : blond female dog -- Parvani finds a homonym -- My father makes a mistake with pronouns -- Protecting rain -- What Mrs. Kushel says -- Good-bye -- The quiet house -- My father has an argument with his brother -- In the middle of the night -- What happened to my mother -- Hud Road -- Author's note.
Middle School
720
Schneider Family Award for Middle School, 2015.
Keywords: Asperger's syndrome -- Juvenile fiction; Dogs -- Juvenile fiction; Lost articles -- Juvenile fiction; Asperger's syndrome -- Fiction; Dogs -- Fiction; Lost and found possessions -- Fiction; Asperger's syndrome; Dogs; Lost articles; Fiction; Juvenile works